Relationship Between Malnutrition Inflammation Score and Dietary Fat Quality Indices with Cardiovascular Diseases in Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2023)
Introductions. Malnutrition-inflammation-atherosclerosis is an independent risk factor and the most significant cause of death in dialysis patients, accounting for about 50% of deaths in the population. Moreover, the high incidence of cardiovascular-induced mortality in patients with end-stage kidney disease cannot be fully attributed to cardiovascular (CVD) risk factors only. Studies suggest that risk factors such as oxidative stress, inflammation, bone disorders, vascular stiffness, and energy protein loss are closely related to CVD and its associated mortality in these patients. Moreover, dietary fat is a crucial factor in CVD. This study focused on determining the relationship between malnutrition-inflammation and fat quality indicators among CKD patients. Methods. This study was conducted on 121 hemodialysis patients aged 20 to 80 years in a teaching hospital affiliated to Hashminejad kidney center in Tehran, Iran during 2020 to 2021. Data on general characteristics and anthropometric indices were collected. The malnutrition-inflammation score was assessed by using MIS and DMS questionnaires and dietary intake was measured by a 24-hour recall questionnaire. Results. Out of 121 hemodialysis patients participating in the study, 57.3% were male and 42.7% were female. Anthropometric demographic characteristics showed no significant difference among diverse groups with heart disease (P > .05). There was no significant relationship between malnutrition-inflammation and heart disease indices in hemodialysis patients (P > .05). Furthermore, there was no correlation between the dietary fat quality index and heart disease (P > .05). Conclusion. In this study, there was no significant relationship between the malnutrition-inflammation index and the dietary fat quality index with cardiac disease in hemodialysis patients. Further studies are needed to have a tangible conclusion.  DOI: 10.52547/ijkd.7280